The Last September: Irish modernism, narrative deferral, historicist determinism. Issue 2 (3rd April 2019) - Greaney, John
ABSTRACT: This article questions the idea that Irish literary modernism is defined by Irish postcoloniality. The continued influence of historicist approaches in literary studies have inspired an understanding of Irish modernism as determined by material base. An oversight of such approaches, however, is that much of the respective fiction which constitutes Irish modernism resists representing the cultural circumstances from which it emerges. Particular to this predicament is Elizabeth Bowen's The Last September given that it is the novel which is often read as representing Ireland's transition from colonial to postcolonial status. Through an analysis of its fractured, and thus typically modernist, narrative strategy, this article argues that colonial history is an absent presence which lacks constitutive meaning in this fiction, and thus suggests that Irish literary modernism does not neatly correspond to or reflect the story of Irish monumental history.